Seeing with both eyes : Ephraim Luntshitz and the Polish-Jewish renaissance - Levin, Leonard, 1946- (Supplements to The Journal of Jewish Thought and Philosophy, 2008)
This is an integrated study of the revival of philosophical studies in 16th-century central-European Jewry focusing on seven major thinkers and especially on the intellectual development of Ephraim Luntshitz (1550-1619). Preoccupation with philosophy is traced through Moses Isserles, Solomon Luria, Mordecai Jaffe, Abraham Horowitz, Eliezer Ashkenazi, Maharal of Prague, and Ephraim Luntshitz. Analysis of these thinkers' intellectual affiliations is based on close analysis of their primary texts, of which a generous selection is provided in translation for the first time. This work advances the scholarly study of 16th-century Polish-Jewish culture, the Polish Jewish Renaissance, the philosophical interests of Ashkenazic Jewry, Jewish responses to Renaissance humanism and the Reformation, and the early-modern background for the 18th-century Jewish Enlightenment.